2013
DOI: 10.1188/13.cjon.335-336
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Oncology Nurses Making the Right Call: Assessment and Education in Telephone Triage Practices

Abstract: Nurses in a hematology/oncology practice are responsible for the triage and management of phone calls from a diverse oncology population. An initiative was developed at the authors' institution to identify the educational needs of RNs while designing strategies to educate and improve telephone triage skills. The goal was to standardize triage practice and ultimately improve the effectiveness of telephone triage management. It was felt that these improvements could enhance the nurse-patient relationship, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…Dependent on speech and delimited nonverbal communication like breathing and vocal pitch, the HCPs endeavoured to identify patients in serious condition and to reach a mutual understanding of the patient's problem without the ability to use all their senses, which in other studies is essential for a clinical decision-making (15,16). Moreover, the HCPs in our study were aware that callers could find it hard to articulate their concerns and occasionally hid them behind verbal hints.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Dependent on speech and delimited nonverbal communication like breathing and vocal pitch, the HCPs endeavoured to identify patients in serious condition and to reach a mutual understanding of the patient's problem without the ability to use all their senses, which in other studies is essential for a clinical decision-making (15,16). Moreover, the HCPs in our study were aware that callers could find it hard to articulate their concerns and occasionally hid them behind verbal hints.…”
Section: Discussionmentioning
confidence: 94%
“…In general, the nature of the patient's problem is assessed by using senses such as seeing, hearing, touching and smelling (15,16). In telephone consultations, HCPs have to rely on auditory cues.…”
Section: Introductionmentioning
confidence: 99%
“…45, No. 2,2022 Ciccolini et al was followed from inception to dissemination of the project findings (Figure 1).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…1 Nurses perform a critical role in telephone triage as they are often the first point of contact and are responsible for proper symptom assessment, management, and subsequent communication with a licensed independent practitioner. 2 Three well-established models have been identified to guide nursing practice, including (1) onset, location, duration, characteristics, aggravating factors, relieving factors, timing, and severity (OLDCARTS), (2) SBAR, and (3) the nursing process. The pneumonic OLDCARTS is a structured approach to eliciting a patient history or history of present illness and conducting a physiologic assessment of the patient's complaint.…”
mentioning
confidence: 99%
“…Gleason et al .,[ 8 ] performed an educational needs assessment of nurses to develop strategies for educating and improving telephone triage skills. The authors found that standardization of triage practice and improvement of triage effectiveness could enhance the nurse-patient relationship, effective continuity of care to the patient, reduce inappropriate appointments and hospitalizations, and reduce the risk of medical complications related to delays in care.…”
Section: Strategies For Ttmentioning
confidence: 99%